Tindakan Komunikatif : Sekilas tentang Pemikiran Jürgen Habermas - Anwar Nuris (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
Benefiting from Jürgen Habermas, an intellectual figure, the study intends to answer two key questions. How is Jürgen Habermas’ epistemologic construction, and what is communicative actions in Habermas’ concept? The answers are next going to include the basic critical theories of Habermas. The beginning part the writing is intended to be the starting point of understanding Habermas’ thought by placing Habermas’ basic epistemology as a basic concept purposed afterward. The writing concludes that the concept of Habermas’ communicative actions is an anchor for all of Habermas’ social theories.Keywords: Jürgen Habermas, Action Rationality, Communicative Action.